Associations between Small Dense LDL, HDL Subfractions (HDL2, HDL3) and Risk of Atherosclerosis in Japanese-Americans - Hirano, Tsutomu; Nakanishi, Shuhei; Maeda, Shusaku; Kohno, Nobuoki; Yoneda, Masayasu; Awaya, Tomokazu; Yamane, Kiminori (Journal of Atherosclerosis and Thrombosis, 2012)
Aim: Small dense low-density lipoprotein (sdLDL) has been suggested to be more atherogenic than large buoyant LDL. High-density lipoprotein (HDL) consists of two major subfractions (HDL2, HDL3), and just as controversy remains regarding which of the two is the more powerful negative risk factor for atherosclerosis, associations between sdLDL and these HDL subfractions are unclear. Methods: We measured sdLDL cholesterol (sdLDL-C), HDL2 cholesterol (HDL2-C) and HDL3 cholesterol (HDL3-C) by a newly developed method in 481 Japanese-Americans who were not using lipid-lowering medication, and examined the associations of these cholesterol concentrations with variables related to atherosclerosis. Results: In multivariate analysis, sdLDL-C was positively correlated with the body mass index (BMI), fasting glucose and insulin, 2-h glucose, HOMA-IR, high sensitivity C-reactive protein (hsCRP), and carotid artery intima-media thickness (IMT) after adjustment for age and sex. In particular, sdLDL-C was positively correlated with IMT, even after adjustment for sex, age, smoking status, hypertension, diabetes mellitus and hsCRP. HDL2-C was more closely inversely correlated than total HDL-C with BMI, fasting glucose and insulin, 2-h glucose, HOMA-IR, and hsCRP, whereas HDL3-C was not correlated with these factors. Additionally, HDL2-C was more closely correlated than total HDL-C or HDL3-C with sdLDL-C, LDL-C, triglycerides (TG), and apolipoprotein B (apoB). Conclusions: SdLDL-C was closely associated with insulin resistance and glucose tolerance, lending credence to its potential as a useful risk marker in assessing carotid artery IMT and the present degree of atherosclerosis in Japanese-Americans. The findings also suggest that subjects with higher HDL2-C levels were better protected from atherosclerosis.